Regulating Cancellation Rights with Consumer Experimentation - Florian Hoffmann; Roman Inderst; Sergey Turlo (ZBW – Leibniz Information Centre for Economics, 2018)
Embedding consumer experimentation with a product or service into a market environment, we find that unregulated contracts induce too few returns or cancella tions, as they do not internalize a pecuniary externality on other firms in the market. Forcing firms to let consumers learn longer by imposing a commonly observed statutory minimum cancellation or refund period is socially efficient only when firms appropriate much of the market surplus, while it backfires otherwise. Interestingly, cancellation rights are a poor predictor of competition, as in the unregulated out come firms grant particularly generous rights when competition is neither too low nor too high.
Keywords: 330